2020
DOI: 10.1021/acs.jced.9b00995
|View full text |Cite
|
Sign up to set email alerts
|

Two-Phase and Vapor-Phase Thermophysical Property (pvTz) Measurements of the Difluoromethane +trans-1,3,3,3-Tetrafluoroprop-1-ene Binary System

Abstract: In this paper, 182 pvTz data (28 data in the two-phase region and 154 data in the superheated vapor region) of mixtures containing difluoromethane (R32) and trans-1,3,3,3-tetrafluoroprop-1-ene (R1234ze­(E)) are reported. The measurements were carried out along 10 isochores (0.013173, 0.039422, 0.043115, 0.046522, 0.062966, 0.068225, 0.068959, 0.110447, 0.115156, and 0.121732 m3·kg–1) in the temperature range from 263 to 373 K for 10 R32 mole fractions (0.1677, 0.2360, 0.2551, 0.4634, 0.5374, 0.6715, 0.7383, 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…These temperatures and pressures covered densities from approximately 2 to 1556 kg·m –3 and included vapor, liquid, and supercritical state points. Data comparisons generally show good agreement with available literature data for the R-32 + R-1234yf, , R-32 + R-1234ze­(E), , and R-1234yf + R-152a blends; no data could be found for the R-1234ze­(E) + R-227ea blend. Comparisons with default mixture models included in REFPROP (version 10.0) showed AADs ranging from 0.368 to 0.445% for the data presented here; in comparison, AADs for available literature data ranged from 0.166 to 3.750%.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These temperatures and pressures covered densities from approximately 2 to 1556 kg·m –3 and included vapor, liquid, and supercritical state points. Data comparisons generally show good agreement with available literature data for the R-32 + R-1234yf, , R-32 + R-1234ze­(E), , and R-1234yf + R-152a blends; no data could be found for the R-1234ze­(E) + R-227ea blend. Comparisons with default mixture models included in REFPROP (version 10.0) showed AADs ranging from 0.368 to 0.445% for the data presented here; in comparison, AADs for available literature data ranged from 0.166 to 3.750%.…”
Section: Discussionsupporting
confidence: 82%
“…; blue ⧖, Tomassetti et al; and gray +, Yang et al For R-32 + R-1234ze­(E): black ○, this work ( x 1 = 0.33512 mole fraction); black □, this work ( x 1 = 0.66665 mole fraction); red △, Jia et al; green ▽, Kobayashi et al; blue ⋈, Tanaka et al; purple ∗, Tomassetti et al. ; and gray +, Yamaya et al For R-1234yf + R-152a: black ○, this work ( x 1 = 0.33342 mole fraction); black □, this work ( x 1 = 0.66526 mole fraction); and red △, Tomassetti . Where needed, the graph region covering the majority of data points has been expanded and is shown in the inset for clarity.…”
Section: Resultsmentioning
confidence: 87%
“…The authors have previously reported vapor phase PvTx data for 12 binary blends of low GWP refrigerants: (1) nitrogen + trans-1,3,3,3-tetrafluoroprop-1-ene, 5 (2) methane + trans-1,3,3,3-tetrafluoroprop-1-ene, 5 (3) propane + 2,3,3,3-tetrafluoroprop-1-ene, 6 (4) propane + cis-1,2,3,3,3-pentafluoroprop-1-ene, 6 (5) isobutane + 2,3,3,3-tetrafluoroprop-1-ene, 7 (6) isobutane + trans-1,3,3,3-tetrafluoroprop-1-ene, 7 (7) isobutane + cis-1,3,3,3-tetrafluoroprop-1-ene, 8 (8) isobutane + trans-1-chloro-3,3,3-trifluoroprop-1-ene, 8 (9) isobutane + cis-1,2,3,3,3-pentafluoroprop-1-ene, 9 (10) isobutane + 3,3,3trifluoropropene, 9 (11) difluoromethane + 2,2,2,3-tetrafluoroprop-1-ene, 10 and (12) difluoromethane + trans-1,3,3,3tetrafluoroprop-1-ene. 11 The present paper expands the authors' work by presenting 150 PvTx measurements for binary blends consisting of difluoromethane (R32) and cis-1,3,3,3-tetrafluoroprop-1-ene (R1234ze(Z)) both in the two-phase and superheated vapor regions using an isochoric test cell. The measured data are correlated with several equations of state, as well as are compared with REFPROP 10.0 12 predictions.…”
Section: ■ Introductionmentioning
confidence: 82%
“…The authors have previously reported vapor phase PvTx data for 12 binary blends of low GWP refrigerants: (1) nitrogen + trans -1,3,3,3-tetrafluoroprop-1-ene, (2) methane + trans -1,3,3,3-tetrafluoroprop-1-ene, (3) propane + 2,3,3,3-tetrafluoroprop-1-ene, (4) propane + cis -1,2,3,3,3-pentafluoroprop-1-ene, (5) isobutane + 2,3,3,3-tetrafluoroprop-1-ene, (6) isobutane + trans -1,3,3,3-tetrafluoroprop-1-ene, (7) isobutane + cis -1,3,3,3-tetrafluoroprop-1-ene, (8) isobutane + trans -1-chloro-3,3,3-trifluoroprop-1-ene, (9) isobutane + cis -1,2,3,3,3-pentafluoroprop-1-ene, (10) isobutane + 3,3,3-trifluoropropene, (11) difluoromethane + 2,2,2,3-tetrafluoroprop-1-ene, and (12) difluoromethane + trans -1,3,3,3-tetrafluoroprop-1-ene …”
Section: Introductionmentioning
confidence: 99%